Sugamadex in the reversal of anaphylaxis due to rocuronium in a pediatric patient: Case report (Research, Society and Development, 2023)
Neuromuscular blockers, notably rocuronium, are a prominent cause of anaphylactic reactions in the perioperative period. Rocuronium, known for its rapid action and intermediate duration, has gained prominence due to the benefits of Sugammadex, its reversal agent, which provides agile and predictable reversal of neuromuscular blockade. We report the case of a 6-year-old patient, weighing 30 kg, who underwent video-assisted thoracoscopic surgery (VATS), who presented an adverse reaction after the administration of rocuronium, manifesting chest flushing, tachycardia, severe hypotension and generalized petechiae. Despite attempts at treatment with adrenaline, there was no improvement in hemodynamics. After administration of Sugammadex, a positive response was observed, with an increase in heart rate and blood pressure, allowing the patient to be transferred to the Pediatric Intensive Care Unit. In this sense, this case report aimed to describe the treatment of an episode of anaphylaxis induced by rocuronium and treated with the administration of sugammadex.